UMP Green Earth Mobility with West Java Community - Siti Sarah, Mohamad Rajimi (2017)
Student Affairs & Alumni Department (Saffad) of Universiti Malaysia Pahang has successfully organized OISCA Sukabumi Green Earth Mobility with the collaboration of Organization for Industrial, Spiritual and Cultural Advancement (OISCA) International Japan, OISCA Training Centre (TC) Sukabumi and SDN 5 Karang Tengah, West Java, Indonesia.